LITERATURE REVIEW : ANALISIS FAKTOR PENYEBAB KETIDAKPATUHAN WAJIB PAJAK MASYARAKAT DI INDONESIA DALAM MEMBAYAR PAJAK - Muhammad Rafael Shauqi Aulia (Pascasarjana Universitas Sultan Ageng Tirtayas, 2022)
We already know that there are still many Indonesian people who are still not satisfied with the construction of facilities built by the government. This indicates that the prosperity and justice that has occurred in the community has not been fully realized. This condition is of course influenced by the disobedience of the community itself as a taxpayer in paying taxes. Therefore, this study describes what factors cause Indonesian people's non-compliance in paying taxes. The research method used in making this scientific paper is a literature review research method with primary sources of journals, literature, and books available in online mass media. The results of the study concluded that the factors of people not being obedient to paying taxes were the lack of awareness in the community, the complicated tax system, and even the subjective norm factor. Also, the tax amnesty influences tax compliance. The government has also made efforts for the public to pay their tax obligations, ranging from socializing the importance of taxes to improving the tax system such as e-filing. The results of this study are expected to be an aspiration to the government regarding what policies should be made and what actions should be taken by the government to improve public compliance in paying taxes.